2013
DOI: 10.1002/chir.22196
|View full text |Cite
|
Sign up to set email alerts
|

Conformational Equilibria of Bridled Chiroporphyrins in Solution Investigated by Vibrational Circular Dichroism

Abstract: A series of bridled chiroporphyrins (BCP) and their metal complexes were prepared, in which two n-methylene straps connect adjacent meso substituents by ester linkages. These compounds can exist as four atropisomers (αααα, αβαβ, αααβ, or ααββ) depending on the position of the meso groups relative to the macrocycle (α when above and β when below). We characterized the conformation of these chiral porphyrins and their metal (Zn, Ni, Mn) complexes by vibrational circular dichroism (VCD) associated with ab initio … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…13 The VCD signals at 1590, 1580, 1560 and 1540 cm −1 are attributable to the stretching vibrations of the C-C in the L 3− . 14 The distinct VCD signals indicated that the crystals of 1 exists in two kinds of enantiomorphism isomers, R for P4 1 32 and S for P4 3 32. The temperature dependence of magnetic susceptibilities of 1 was measured from 2 to 300 K with 1000 Oe.…”
mentioning
confidence: 99%
“…13 The VCD signals at 1590, 1580, 1560 and 1540 cm −1 are attributable to the stretching vibrations of the C-C in the L 3− . 14 The distinct VCD signals indicated that the crystals of 1 exists in two kinds of enantiomorphism isomers, R for P4 1 32 and S for P4 3 32. The temperature dependence of magnetic susceptibilities of 1 was measured from 2 to 300 K with 1000 Oe.…”
mentioning
confidence: 99%
“…VCD has allowed the re-examination of the AC of some natural products like ()-brevianamide [6] and (+)-schizandrin [7], and it has eventually aided the re-examination and reassignment of the molecular structure of klaivanolide [8]. The VCD superiority over other spectroscopic methods has allowed the structural analysis of complex molecules, like the atropisomer distribution of bridled chiroporphyrins in solution [9], or the planar configuration of nonaand dodecamethoxycryptophanes [10]. It also has been used to determine the secondary structure of NH-indazoles such as (4S,7R)campho [2,3-c]pyrazole [11].…”
mentioning
confidence: 99%
“…24 The VCD couplets at 1560, 1540, 1520, 1510 and 1490 cm À1 are assigned to the antisymmetrical stretching of the CQN bond and skeleton vibrations of the aromatic rings in the ligand of L 3À in III, 25 while the VCD couplet at about 1450 cm À1 is ascribed to the bending vibrations of the methylene (dCH 2 ) or methyl (dCH 3 ) groups in III. 26 It was mentioned that the distinct VCD signals observed in III indicate that VCD spectra are a remarkable complementarity that can be used as an advantage when a particular system is investigated by the selection of chiroptical procedures.…”
mentioning
confidence: 99%